Isolation and identification of tyramine-producing bacteria and their biogenic amines formation during fermentation of sufu - Li, Yuwei; Yan, Tingting; Yin, Lijun; Cheng, Yongqiang; Jia, Xin (Cellular and Molecular Biology, 2022)
The Chinese traditional soybean product, sufu, is getting increasingly popular in Asia for its special taste and rich nutrition. In this paper, physicochemical properties of sufu during fermentation, isolation and characterization of BA-producing bacteria, as well as their decarboxylase activities were thoroughly investigated. Tyramine, putrescine, phenylethylamine and cadaverine were the main BA in sufu fermentation. Tyramine level increased drastically to reach 513.72 mg/kg during sufu ripening, posing potential health risks. During sufu fermentation, there was a positive correlation between amino nitrogen and BA, yet no significant correlation was found between BAs with pH and total acidity. Additionally, 23 strains of tyramine- and phenylethylamine-producing bacteria harboring the TDC gene, including Enterococcus faecalis 45, Enterococcus faecium 36, Pediococcus acidilactici 310 and Pediococcus pentosaceus 27 that were responsible for tyramine production in sufu have been characterized. The current study provides insights into understanding the production of tyramine in sufu by microorganisms, which laid the groundwork for controlling biogenic amine production in fermented soybean products.